THE USEFULNESS OF ENGLISH BREAKING APLICATIONS FOR EFL LEARNERS VOCABULARY - Fitria, Nadiya; Siregar, Deasy Yunita (JURNAL KONFIKS, 2025)
In today’s digital era, technology plays an increasingly vital role in language learning, particularly for EFL (English as a Foreign Language) learners who often struggle with conventional classroom methods. This study explores the effectiveness of the English Breaking application in enhancing vocabulary acquisition among EFL students. Using a qualitative case study approach, data were gathered from in-depth interviews with university students in Medan who used the app for one month. The findings indicate that English Breaking positively influenced learners' vocabulary development, motivation, and engagement through its interactive flashcards, adaptive pronunciation tools, and gamified learning features. However, users also reported technical challenges, such as unstable internet requirements and unclear navigation. Despite these issues, the app's capacity to support personalized and autonomous learning proves promising. The study underscores the app’s potential as a supplementary language learning tool and calls for improvements in technical performance and social interactivity features. These findings hold significant implications for educational app developers, language educators, and policymakers aiming to optimize digital learning environments for EFL contexts.